Development of Attitude Assessment Instruments on Learning Text Report Observation Results for 7th Grade Students Smp Swasta Taman Harapan Medan - Dewi Wahyuni; M. Oky F.Gafari; Daulat Saragi (Budapest International Research and Critics University, 2019)
This study aims to describe the pattern of development, validity and feasibility and effectiveness of attitude assessment instruments on learning the text of observational reports for grade VII students SMP Swasta Taman Harapan Medan. Research instruments in the form of questionnaires and observation sheets. The assessment instrument developed in this study was an attitude assessment instrument in the form of a self-assessment test. The results of the field trials show that the results of the material expert's assessment of the instrument's worth were 89.17% and were valid qualifications. While the evaluation of expert evaluation results obtained a percentage of 88.57% and are in valid qualifications. Based on the results of trials that have been carried out, it can be stated that the attitude assessment instruments developed already have good validity so that they are suitable for use in learning assessment activities. In the field trial phase the researchers tested the level of students' understanding ability to see the level of effectiveness of the assessment instrument for attitude assessment. Based on the analysis results obtained an average ability of students' attitudes/affective that is 76.46% with a good category. The results obtained in this study indicate that self-assessment instruments can measure the ability of student attitudes and provide instructions that in learning Indonesian by using self-assessment instruments are more appropriate to be applied in learning so that teachers can further evaluate the advantages and disadvantages of learning received by students.